Inter-Cultural Communication: Sipakatau-Sipakalebbi Among Bugis-Kaili Couples in Palu - Sitti Murni Kaddi; Andi Akifah (Komunikator, 2023)
This article investigates intercultural marriage from the perspective of communication between ethnic Bugis (migrants) and ethnic Kaili (natives) in Palu City, Central Sulawesi. This study seeks to analyze and investigate the cultural principle of sipakatau-sipakalebbi (mutual respect and humanization) among married Bugis and Kaili couples in Palu City. Through an examination of the patterns and practices of intercultural communication and family communication through the lens of Indonesian local culture, this research contributes to the Relational Dialectic Theory using a case study methodology. The empirical findings of this study indicate that the sipakatau culture (mutual humanization) and the sipakalebbi principle (mutual respect), which are the guiding principles and communication strategies of Bugis ethnics, are still adhered to in their interactions with others, even though many of them are married to individuals of different cultural and ethnic backgrounds. This study also found that Bugis and Kaili inter-ethnic marriage partners understand the dynamics and communicate all the dynamics concerning these cultural differences, allowing for the resolution of problems and estrangement, including those that contribute to marital conflict. Due to a lack of comprehension of the sipakatau sipakalebbi principle on the part of Kaili couples, this principle has yet to satisfy Bugis couples in practice.